Fine particulate matter induces mitochondrial dysfunction and oxidative stress in human SH-SY5Y cells. (March 2019) - Wang, Ying; Zhang, Mei; Li, Zhiping; Yue, Jianwei; Xu, Min; Zhang, Yanhao; Yung, Ken Kin Lam; Li, Ruijin
Abstract: Exposure to ambient fine particulate matter (PM2.5 ) is associated with neurodegenerative diseases. Mitochondrion is key to brain degeneration. However, the underlying mechanism of PM2.5 -induced brain injury, especially mitochondrial damage, is still unclear. In this study, changes in mitochondrial dynamics, mitochondrial permeability transition pore (mPTP), mitochondrial DNA (mtDNA) and oxidative stress in human SH-SY5Y cells exposed to PM2.5 at different concentrations (0, 25, 100, and 250 μg mL −1 ) were investigated. The results showed that PM2.5 caused more mitochondrial swell, accompanied by the opening of mPTP and the decrease of ATP levels, mitochondrial membrane potential and mtDNA copy number in SH-SY5Y cells. PM2.5 significantly enhanced the expression of mitochondrial fission/fusion genes (Drp1 and OPA1) and affected the gene expression of CypD, SIRT3, and COX Ⅳ in SH-SY5Y cells. Besides, PM2.5 triggered the increase of cellular ROS, Ca 2+ and Aβ-42 levels, inhibition of manganese-superoxide dismutase (SOD2 ) activities, reduction of GSH levels GSH/GSSG ratio, and elevation of mitochondrial malondialdehyde contents. It suggests that mitochondrial dysfunction and oxidative stress are the potential mechanisms underlying PM2.5 -induced brain nerve cell injury, which may be related to neurological diseases. Additionally, our study elucidated that PM2.5 components trigger different cytotoxicity. Graphical abstract: Image 1 Highlights: PM2.5 induces mitochondrial morphological damage of SH-SY5Y cells. PM2.5 triggers mitochondrion permeability transition pore opening. PM2.5 reduces ATP, mitochondrial membrane potential and mtDNA copy number. PM2.5 -caused oxidative stress related to enhancement of ROS, SIRT3 and Aβ-42 levels.